THE EFFECT OF PHYSICAL ACTIVITY AND ANXIETY LEVEL OF TRIMESTER III MOTHERS ON INFANT’S BIRTH BODY WEIGHT - Emi Barus (Nusantara Medical Science Journal, 2016)
ABSTRACTIntroduction: One  of the causes of infant  death  in Indonesia is complications from baby’s birth weight, this complication can be prevented and managed to reduce infant mortality rate. The aims of the research were to determine the types of physical activi- ties,  anxiety levels,  and  cortisol level  of trimester III pregnant women, the effect  of physical activity on infants’ birth body weight, the effect of anxiety and cortisol levels on infants’ birth  body  weight, and the effect  of anxiety on cortisol level.  Methods: The research was a longitudinal study conducted in Rumah Sakit Kesehatan Daerah Ibu dan Anak  (RSKDIA) Siti Fatimah, Makassar. The  subjects were  trimester pregnant women selected using purposive sampling technique consisting of 55 people. The data were analyzed using chi-square test. Results: The results of the research indicate that the respondents who did light-mild physical activities were 35 people (63.6%) generally gave birth to normal birth body weight, while ones who did strenuous activity were 20 people  (36.4%) gave birth to low birth weight  (LBW)  infants. Respondents with light- mild anxiety consisting of 35 people  (63.6%) generally gave  birth to normal infants, while the ones with severe  anxiety consisting of 20 people  (36.4%) gave birth to LBW infants. Meanwhile, respondents with normal cortisol level gave  birth to normal birth body weight infants, i.e. 35 people  (63.6%), while the ones with high cortisol level con- sisting  of 20 people  (36.4%) gave  birth  to LBW  infants. Conclusion: Based  on the results, there was an effect of physical activities, anxiety levels,  and cortisol level on infants’ birth body weight. Keywords: physical activity, anxiety levels, cortisol, infants’ birth body weight